Morphological optic nerve changes in a patient who has not undergone surgery for her giant pituitary adenoma: a case report (Ukrainian Journal of Ophthalmology, 2024)
We report a lethal case of a female patient who has not undergone surgery for her giant invasive infrasellar/endosellar/suprasellar/parasellar/retrosellar pituitary adenoma. The paper presents results of histological examination of optic nerves and considers the mechanisms of vision loss in prolonged chiasmal and optic nerve compression.
Keywords: pituitary gland; anterior pituitary tumors; compressive optic neuropathy; pathohistological changes; invasive expansion